2020
DOI: 10.3171/2019.4.jns1912
|View full text |Cite
|
Sign up to set email alerts
|

Operculoinsular cortectomy for refractory epilepsy. Part 1: Is it effective?

Abstract: OBJECTIVEPatients with refractory epilepsy of operculoinsular origin are often denied potentially effective surgical treatment with operculoinsular cortectomy (also termed operculoinsulectomy) because of feared complications and the paucity of surgical series with a significant number of cases documenting seizure control outcome. The goal of this study was to document seizure control outcome after operculoinsular cortectomy in a group of patients investigated and trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(21 citation statements)
references
References 39 publications
3
17
1
Order By: Relevance
“…Despite historical high morbidity rates associated with surgery for IE, 39 modern reports demonstrate that IE surgery can be carried out with moderate permanent morbidity. 16,27 Overall, 42% of patients undergoing surgery for IE experienced neurological deficits in our study, but only a reasonably small fraction of these complications were permanent (7.8% of all surgically treated patients). Additionally, the vast majority of patients who exhibited transient deficits recovered rapidly (68.9% within 3 months).…”
Section: Safety Of Insular Epilepsy Surgerymentioning
confidence: 60%
See 2 more Smart Citations
“…Despite historical high morbidity rates associated with surgery for IE, 39 modern reports demonstrate that IE surgery can be carried out with moderate permanent morbidity. 16,27 Overall, 42% of patients undergoing surgery for IE experienced neurological deficits in our study, but only a reasonably small fraction of these complications were permanent (7.8% of all surgically treated patients). Additionally, the vast majority of patients who exhibited transient deficits recovered rapidly (68.9% within 3 months).…”
Section: Safety Of Insular Epilepsy Surgerymentioning
confidence: 60%
“…These studies have shown IE surgery to be feasible, albeit with variable seizure freedom rates and a non‐negligible neurological morbidity profile. Consequently, widespread adoption of IE surgery has been hampered, primarily due to concerns of its efficacy 16 and safety 34 profile and perceived “unfavorable risk‐to‐benefit ratio” 34–36 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Around one third of the patients experienced a temporary paresis. Gireesh et al, reported one intracerebral hematoma following LITT that required a decompressive hemicraniectomy, but subsequently had a good outcome ( 26 , 34 ). Bouthillier et al, recently published the results of 44 insulo-opercular cortectomies in 43 patients achieving a an Engel class 1 outcome in 77% (mean follow-up 6 years) with a 7% permanent postoperative deficit.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, an icEEG recording was performed in eight OIE and one TLE participants. In order to specifically study OIE, we only selected patients who had a favorable outcome following a partial or radical insular resection with or without an operculectomy [34,35] (Engel class I for seven patients and II for two patients; mean follow-up time 4.2 ± 1.3 years). Similarly, to ensure confident focus localization, all patients in the TLE group had to have unilateral hippocampal sclerosis and good outcome after anterior temporal lobectomy (Engel class I at last follow-up; mean follow-up time 3.1 ± 1.6 years).…”
Section: Participantsmentioning
confidence: 99%